1999
DOI: 10.1046/j.1365-2109.1999.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance response to ammonia and nitrite exposure in larvae of two marine fish species (gilthead seabream Sparus aurata L. and Senegal sole Solea senegalensis Kaup)

Abstract: Gilthead seabream Sparus aurata L. and Senegal sole Solea senegalensis Kaup are two species of ®sh that are of primary importance in Mediterranean aquaculture. In the present study, the larvae of these species were exposed to different concentrations of total ammonia and nitrite for 24 h to examine the toxicity of both nitrogenous compounds to larvae under rearing conditions. The non-ionized ammonia (NH 3 ) and nitrite (NO 2 ± ) 24-h LC 50 values were 0.24 p.p.m. and 1997 p.p.m., respectively, in 12day-old S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
2
27
1
Order By: Relevance
“…The growth rate for larvae has been increased gradually with increasing temperature until 20 °C then decreased. These results agreed with most studies on biological development and temperature in Senegal sole as many authors have used a constant temperature of 20 ºC (Martinez et al, 1999;Parra and Yufera, 1999;Ribeiro et al, 1999;Yufera et al, 1999;Canavate et al, 2006;Sanchez et al, 2010;Salas-Leiton et al, 2011, 2012. The Senegal sole (Solea senegalensis) is a flatfish adapted to temperate waters of around 20-21 ºC (Drake et al, 1984).…”
Section: Effect Of Temperaturesupporting
confidence: 80%
“…The growth rate for larvae has been increased gradually with increasing temperature until 20 °C then decreased. These results agreed with most studies on biological development and temperature in Senegal sole as many authors have used a constant temperature of 20 ºC (Martinez et al, 1999;Parra and Yufera, 1999;Ribeiro et al, 1999;Yufera et al, 1999;Canavate et al, 2006;Sanchez et al, 2010;Salas-Leiton et al, 2011, 2012. The Senegal sole (Solea senegalensis) is a flatfish adapted to temperate waters of around 20-21 ºC (Drake et al, 1984).…”
Section: Effect Of Temperaturesupporting
confidence: 80%
“…According to Person-Le Ruyet (1997), unionized ammonia (NH 3 ) corresponds to 2-4% of TAN in saltwater. Using these reference values, the concentration of NH 3 obtained for the higher value observed in the present study corresponds to 0.03-0.05 mg NH 3 L -1 , well below the value of 0.13 mg L -1 recommended by Parra and Yúfera (1999) to prevent deaths.…”
Section: Discussionmentioning
confidence: 90%
“…The TAN concentration in water was kept lower than 1 mg L -1 for both treatments, although postlarvae from the Artemia treatment were exposed for two hours above this value (1.28 mg TAN L -1 ). Parra and Yúfera (1999) observed that total mortality was attained when Senegalese sole larvae were exposed to 80 mg L -1 of ammonia (TAN). Based on water temperature, oxygen and pH, these authors calculated a 24-h LC 50 (NH 3 ) of 1.32 mg L -1 for this species (1.6% of TAN).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To highlight this, two examples have been chosen, although many more are likely to exist within the literature: (i) aquaculture studies; and (ii) airsea NH 3 flux studies. These examples have been chosen in part because many research groups (including our own) have used the Khoo et al [1] equation as part of aquaculture studies [12,13] and air-sea NH 3(g) exchange studies. [14][15][16] (i) It has been shown that NH 3 is toxic to many organisms above certain threshold levels.…”
mentioning
confidence: 99%